Размышления по поводу языковой интерпретации при обучении студентов-русистов - Ясаи, Ласло (SlavVaria, 2024)
Reflections on Linguistic Interpretation in the Teaching of Russian as a Foreign Language. The subject of this article is the different grammatical forms of verbal action that can create a synonymous relationship with another grammatical form of the verb. In the case of such grammatical synonymy, interpretative differences come to the forefront. The author aims to draw attention to the importance of such differences and present their features from the point of view of mode of expression. When analyzing the phenomenon of grammatical interpretation, the main emphasis is on the verbal categories of voice, aspect and tense. In addition, special attention is paid to the forms of verbal adverbs in comparison with the verbal predicate of the main action.